Water stress inducible proline transporter from Indica rice - Khomdram, Sushma; Barthakur, Sharmistha; Devi, G.A. Shantibala (Annals of Agricultural Research, 2014)
The accumulation of osmoprotectant such as proline is an important process for the adaptation to adverse environmental conditions. The increase of osmoprotectants is achieved either by altering metabolism or by its transport. Plant proline transporters belong to the amino acid/auxin permease (AAAP) sub family of plant amino acid transporter (AAT) super family. We identified four putative proline transporters in indica rice by sequence homology search. With an objective to clone proline transporter genes and cDNAs from rice, we used a drought tolerant indica cultivar N22 and carried out a transcript expression profiling after imposing water stress. A 1.2kb genomic fragment and a 900bp cDNA of two different indica rice proline transporters was PCR/RTPCR amplified, cloned in pGM-T-easy vector, sequenced and characterized.